Second-best optimal taxation of oil and capital in a small open economy - Alberto Petrucci (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper analyzes the efficient taxation of oil and capital income in an oil-dependent infinite-lived economy facing perfect capital mobility. Two cases are examined: one with product market imperfections and free tax choice, one with perfect competition and tax restrictions. The optimal tax rates on oil and capital strictly depend on the international tax system implemented; however, they are also affected by the degree of market power and the extent to which monopoly profits are taxed, the type of tax restrictions and the use of oil (as an input or a consumer good). Under the residence-based system, capital income should always be exempted from taxation, while the optimal tax on productive oil may differ from zero. Under the source-based system, second-best taxes on capital and oil are non-zero.
Keywords: E62; H21; Q43; Q48; 330; Optimal Factor Taxation; Oil; Capital Income; Residence-based System; Source-Based System; Kapitalertragsteuer; Erdöl; Verbrauchsteuer; Optimale Besteuerung; Kleines-offenes-Land; Steuertheorie